Drought sensitivity of Empetrum nigrum shrub growth at the species’ southern lowland distribution range margin - Hein, Nils; Merkelbach, Julia; Zech, Katharina; Weijers, Stef (Plant Ecology, 2021)
The ongoing warming of the Earth’s atmosphere is projected to cause a northward shift of species’ distributions, as they track their climatic optimum. In the rapidly warming Arctic, this has already led to an increase of shrubs in tundra ecosystems. While this northern expansion of woody biomass has been studied relatively extensively over the last decade, little research has been devoted to shrub growth responses at the southern margins of Northern Hemisphere shrubs. Here, we studied shoot length growth, its responses to climate over the period 2010–2017, and differences in leaf C and N content of the evergreen dwarf shrub Empetrum nigrum, as well as the vegetation composition and soil parameters at four sites located along a gradient of increasing dune age on the island Spiekeroog, northern Germany. The sites are located in the tri-national UNESCO world heritage site, the Wadden Sea. E. nigrum has a predominantly circum-arctic-boreal distribution and its southern distribution margin in European lowlands runs through northern Germany, where it is retreating northwards. We found a negative response to autumn (surface) temperatures and previous summer surface temperatures and/or a positive response to summer precipitation of E. nigrum growth, except at the oldest dune with the strongest E. nigrum dominance. Growth rates and plant species diversity declined with dune age. Our results suggest that E. nigrum growth is drought sensitive at its European southern range margin. We hypothesize that this sensitivity may form the basis for its northward retreat, which is supported by recent observations of E. nigrum dieback in Germany after the extreme drought in 2018 and model projections.